MANAGEMENT OF NON PHARMACOLOGICAL PAIN IN CLIENTS WITH RHEUMATHOID ARTHRITIS : A LITERATURE REVIEW - Wekoadi, Galih Mahendra; Widiyanto, Budi (Journal of Applied Health Management and Technology, 2020)
Rheumathoid Arthritis is a disease that occurs due to abnormalities in the joints, causing pain and stiffness in the musculoskeletal system such as skeletal muscles, joints, ligaments and bones and generally attacks clients over the age of 40 years (Syapitri, 2018). Rheumatoid Arthritis has typical symptoms in sufferers, one of which is pain. If not handled properly, pain in rheumathoid arthritis can disrupt the activities of sufferers, paralysis and impaired balance. Therefore, pain in reumathoid arthritis must be treated. The aim of writing this literature review is to provide information about the non-pharmacological management of pain in clients with rheumatoid arthritis. The method used in this study is to use the Literature review method. Literature review is carried out by analyzing articles relevant to the title taken, namely the management of non-pharmacological pain in clients with Rheumathoid arthritis. The stages in conducting a Literature review are based on 5 stages of literature review that cover the eligibility criteria, information sources, selection of literature, data collection and selection of data items. With pain rheumatic arthritis include: back massage, cupping, benson relaxation and warm compresses, cinnamon compresses, giving of the gnome, ginger compresses, lemongrass compresses, Swedish massases, giving keroncong music, grated ginger grater, tai chi exercise, and yoga interventions.